Ismail al Faruqi’s Interfaith Dialogue and Asian Religions with Special Reference to Buddhism (American Journal of Islam and Society, 2011)
This study looks at the suitability and relevance of al Faruqi’s dialogical ideas in relation to Asian religions, with special reference to Buddhism. The primary weakness in Faruqi’s dialogical and meta-religious principles in relation to Asian religions lies in his methodological exclusion of mystical and esoteric contributions, insights, and perspectives. Thus, a rational approach to dialogue needs to be combined with other approaches. There is a leeway for al Faruqi’s principles to be shaped and deepened further, and this continues to remain one aspect of his legacy.